PM.64 Pregnancy Outcomes in Women with Sickle Cell Disease at a London Hospital (2006–2012). (26th April 2013) - Ip, J; Parisaei, M; Dorman, E; Erskine, K; Ahmed, T; Amos, R
Abstract : Introduction: SCD is associated with both maternal and fetal complications including pre-eclampsia, growth restriction and stillbirth together with an increased frequency of acute painful crises. Method: This was a 6-year retrospective audit of 56 pregnant women with SCD: 22 HbSS & HbS-beta(0); 27 HbSC; 7 HbS-beta(+). Setting: The women were all managed by the same multidisciplinary team, which included haematolgists, obstetricians and a specialist SCD midwife. Results: There were few obstetric antepartum complications (2% pre-eclampsia, 2% antepartum haemorrhage). However, 35% were admitted with acute painful crises. 7 women underwent regular exchange transfusions for severe pre-existing maternal disease and significant obstetric history. There were no maternal deaths in this cohort. 9% of women with SCD were delivered before 34 weeks. 64% of women were delivered by caesarean section (61% emergency, majority of which were for failure to progress). Out of the 56 pregnancies, there were 54 live births, 2 stillbirths (one unexplained at 40 weeks, one with severe growth restriction at 27 weeks), and 1 neonatal death (day 8 secondary to disseminated herpes simplex). Discussion: The Green-top Guideline (No.61, 2011) suggests all those with SCD should be on low dose aspirin from 12 weeks, have appropriate management of painful crisis and undergo extra scanning with uterine artery dopplers. Most of these pregnancies predate this RCOG guideline. It would be interesting to note if further improvements in outcome will follow recent recommendations. SCD is the commonest and fastest growing single gene genetic disorder in the UK and these women benefit from specialised multidisciplinary care.